Amputation and mortality frequencies associated with diabetic Charcot foot arthropathy: a meta-analysis. Issue 8 (December 2022) - Yammine, Kaissar; Boulos, Karl; Assi, Chahine; Hayek, Fady
Abstract: Background: Five-year mortality and amputation frequencies after new-onset diabetic ulceration have been reported up to 55% and 74%, respectively. for patients with lower-extremity amputation. Following Charcot arthropathy, these frequencies were reported with wide variations. The aim of this meta-analysis is to provide a quantitative evaluation of amputation and mortality frequencies in a diabetic patient with a Charcot foot arthropathy. Methods: Electronic search strategy was applied on Medline, Web of Science, Cochrane Library and Google Scholar since inception to December 2021. Extracted data included study design, sample and patients characteristics, diabetes type and duration, lab results, ulcers at diagnosis, co-morbidities and follow up period. Meta-analysis reporting random-effects values was used to generate the weights results. Results: A total of 16 studies were included in the quantitative meta-analysis with a pooled sample of 2250 patients with 2272 Charcot feet. Two studies including 255 patients yielded a 1-year mortality frequency of 4% (95% CI = 0.018–0.065). Seven studies including 1706 patients reported a 5-year mortality frequency of 24.5% (95% CI = 0.172–0.326, I² = 88.5%). Four studies including 277 patients yielded a seven plus year mortality frequency of 16% (95% CI = 0.065–0.289, I² = 84.3%). Ten studies including 871 foot yielded an amputation frequency of 15% (95% CI = 0.067–0.258, I² = 93.6%) where 9% where major amputations (95% CI = 0.062–0.127, I² = 60%) and 5% were minor amputations (95% CI = 0.004–0.126, I² = 94.7%) Conclusion: Diabetic Charcot arthropathy yields marked risk of amputation and mortality. However, mortality frequencies were unexpectedly lesser compared to those related to the published frequencies associated with diabetic foot ulcers.